3D-printed guides for cervical pedicle screw placement in primary spine tumor: Case report and technical description - Marengo, Nicola; Di Perna, Giuseppe; Baldassarre, Bianca Maria; Cofano, Fabio; De Marco, Raffaele; Zeppa, Pietro; Petrone, Salvatore; Ajello, Marco; Garbossa, Diego; Zenga, Francesco (Frontiers in Surgery, 2022)
Dealing with unstable cervical spine has been usually challenging for spine surgeons and this becomes more difficult when facing a primary cranio-vertebral junction tumor. Primary spine tumors surgery should always include column reconstruction in order to guarantee biomechanical stability of the spine, but surgeons should always be aware that instrumentations could create interferences with postoperative radiations. However, although carbon fiber instrumentations have started to be used in thoracolumbar oncology since few years, these options are still not available for cervical spine. In the reported case, the adopted strategy to obtain adequate column reconstruction was based on the idea of reducing the amount of titanium needed for posterior fixation and maximizing the distance between the radiation target and titanium rods. A case of a 53 years-old woman harboring a cranio-vertebral junction chordoma is presented. A short occipito-C3 construct was selected. Specifically, titanium cervical pedicle screws were placed by using a new technology consisting in patient tailored and customized 3D-printed guides. The aim of this case report is to describe the feasibility and safety of 3D-printed guides for CPS positioning even in a case of cervical spine tumor. CPS could represent a good solution by providing strong biomechanical purchase and tailored 3D printed guides could increase the safety and the accuracy of this challenging screw placement, even in oncological patients